외국인 템플스테이 체험에 대한 국제포교사의 인식 연구 - 오정민(Jeong Min Oh) (융합관광콘텐츠연구, 2025)
목적 이 연구는 코로나19 이후 재충전과 휴식을 위한 관광프로그램으로 주목받고 있는 템플스테이의 가치에 주목하고, 외국인 템플스테이 참여 확대를 위한 시사점을 제시하는 것을 목적으로 한다. 방법Q방법론을 적용하여 외국인 템플스테이 경험의 주관성을 구체화하고, 각 유형의 특징을 분석하였다. 구체적으로 문헌고찰 및 비구조화된 인터뷰를 실시하여 최종 36개의 Q진술문을 확정하고, 외국인 참가자와 접점에서 소통하며 활동하고 있는 국제포교사 30명을 P표본으로 하였다. 결과 분석 결과 총 4가지 인식 유형이 도출되었다. 제1유형은 ‘사색과 치유의 템플, 힐링스테이 선호형’으로, 방해받지 않는 조용한 휴식을 중시하는 유형이다. 제2유형은 ‘다시 찾는 템플, 지속 가능한 스테이 전략형’으로, 사찰별 특화된 프로그램의 필요성을 높게 인식했다. 제3유형은 ‘스님과 함께 하는 템플, 체험 가치 강화형’으로, 스님과 함께 하는 명상 및 차담 시간에 대한 만족도가 높으며, 이를 토대로 주지스님을 비롯한 사찰 종무원의 프로그램 운영 역량 강화 필요성을 제기했다. 제4유형 ‘다양성이 살아 있는 템플, 글로컬스테이 추구형’은 외국인 참가자의 문화적 다양성을 배려할 수 있는 물리적 시설과 자연경관 등 환경적 요소의 중요성을 강조했다. 결론 이 연구는 템플스테이가 한국을 대표하는 문화관광상품으로 자리잡을 수 있도록 연구의 외연을 확장하는 데 기여할 것이며, 템플스테이 프로그램의 국제 경쟁력 강화를 위한 기초 자료로 활용될 수 있을 것이다. Purpose This study aims to focus on the value of temple stay, which has been gaining attention as a tourism program for recharging and relaxation after COVID-19, and to provide implications for expanding the participation of foreigners in temple stay. Methods By applying Q methodology, the subjectivity of foreign temple stay experiences was specified and the characteristics of each type were analyzed. Specifically, 36 Q statements were finalized through a literature review and unstructured interviews, and 30 international missionaries who communicate with foreign participants and work nationwide were selected as P samples. Results The analysis results revealed four types of perception. Type 1 is ‘temples for contemplation and healing, healing stay preference’, which wants a quiet rest without interruption. Type 2 is ‘temples to visit again, sustainable stay strategy type’, which highly recognized the need for specialized programs for each temple. Type 3, ‘temples with monks, strengthening experience value’, emphasized the high response to meditation and tea time with monks and suggested strengthening the program operation capacity of temple administrators including the head monk. Type 4, ‘temples with alive diversity, global stay pursuit’, recognized the influence of environmental factors such as physical facilities and natural landscapes that can take into account the cultural diversity of foreign participants. Conclusion It will contribute to the external expansion of temple stay research so that it can become a representative cultural tourism product of Korea, and will serve as a foundation for strengthening the international competitiveness of the temple stay program. KCI Citation Count: 0